White wine technology - Morata, Antonio (Academic Press, 2022)
Key Features- Covers trends in in both traditional and modern enology technologies, including extraction, processing, stabilization and ageing technologies- Examines the potential impacts of climate change on wine quality- Provides an overview of biotechnologies to improve wine freshness in warm areas and to manage maturity in cold climates- Includes detailed information on hot topics such as the use of GMOs in wine production, spoilage bacteria, the management of oxidation, and the production of dealcoholized wines.